1999
DOI: 10.1073/pnas.96.9.5077
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial sequences show diverse evolutionary histories of African hominoids

Abstract: Phylogenetic trees for the four extant species of African hominoids are presented, based on mtDNA control region-1 sequences from 1,158 unique haplotypes. We include 83 new haplotypes of western chimpanzees and bonobos. Phylogenetic analysis of this enlarged database, which takes intraspecific geographic variability into account, reveals different patterns of evolution among species and great heterogeneity in species-level variation. Several chimpanzee and bonobo clades (and even single social groups) have ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
169
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(192 citation statements)
references
References 62 publications
18
169
2
3
Order By: Relevance
“…50,51 The pattern 221 of dispersal has clearly contributed to contemporary human diversity, mediated by the 222 regional geographical routes taken, contrasting selective pressures, and periodic local 223 isolations, all of which have promoted inter-group differences and some genetic 224 diversification. 52,53 Despite this, our species is characterised by remarkably high levels of 225 genetic unity, 54 fundamentally linked with our high levels of phenotypic plasticity. The 226 selective pressures that favoured the capacity to tolerate ecological instability during 227 hominin evolution have made modern humans extremely well adapted to colonising diverse 228 environments.…”
Section: The Emergence Of Population Variability 215mentioning
confidence: 99%
“…50,51 The pattern 221 of dispersal has clearly contributed to contemporary human diversity, mediated by the 222 regional geographical routes taken, contrasting selective pressures, and periodic local 223 isolations, all of which have promoted inter-group differences and some genetic 224 diversification. 52,53 Despite this, our species is characterised by remarkably high levels of 225 genetic unity, 54 fundamentally linked with our high levels of phenotypic plasticity. The 226 selective pressures that favoured the capacity to tolerate ecological instability during 227 hominin evolution have made modern humans extremely well adapted to colonising diverse 228 environments.…”
Section: The Emergence Of Population Variability 215mentioning
confidence: 99%
“…Four chimpanzee subspecies with nonoverlapping geographic ranges have been proposed on the basis of genetic differences in mitochondrial DNA sequences (Morin et al 1994;Gonder et al 1997;Gagneux et al 1999). We amplified and sequenced a 498-bp fragment of mitochondrial DNA displacement loop (mtDNA D-loop) for the 15 chimpanzees infected by PanRHV1a, PanRHV1b, or PanRHV2.…”
Section: A Novel ␥2-herpesvirus In Common Chimpanzeesmentioning
confidence: 99%
“…In an analysis of variation in the mitochondrial DNA (inherited from mother), Gagneux et al (1999) found considerably less variability in human populations than in populations of other African hominoids. The restricted variability indicates that "something unusual happened in the early history of our species" (Gagneux et al, 1999, p. 5081), including the possibility of repeated bottlenecks and selective populations sweeps -that is, repeated expansions and contractions of early human populations.…”
Section: Figurementioning
confidence: 98%
“…In an analysis of variation in the mitochondrial DNA (inherited from mother), Gagneux et al (1999) found considerably less variability in human populations than in populations of other African hominoids. The restricted variability indicates that "something unusual happened in the early history of our species" (Gagneux et al, 1999, p. 5081), including the possibility of repeated bottlenecks and selective populations sweeps -that is, repeated expansions and contractions of early human populations. This cyclical pattern operating in the context of the changes in hominid social structure (e.g., coalition-based male -male competition) creates a mechanism that could result in hand-over-hand coevolutionary change in traits that support social competition, including brain size, social competencies, length of the developmental period, and intensive parenting.…”
Section: Figurementioning
confidence: 98%